Income Analysis And Optimization Of Cow Livestock Development In Supporting The Livestock Development Program In Kupang Regency - Nikson Tameno; Aldarine Molidya; Decembry C. Nope (Eduvest - Journal of Universal Studies, 2021)
This study aims to answer the main problem regarding income and optimization of cattle husbandry development in supporting livestock development programs in Kupang Regency. The research method used is social qualitative research method with FGD pattern to obtain primary and secondary data. This research took place in Kupang Regency as an area that has potential for cattle which is always in demand by other regions such as DKI Jakarta and so on. If viewed from the prospect of Beef Cattle Development in Kupang district, then look for markets for livestock and livestock products both from NTT and within NTT itself continue to increase in line with economic growth and population growth. There is still a lot of land that is available and possible for the development of livestock business which has not been utilized. The government's policy of encouraging state-owned enterprises to mediate funds to assist small businesses and at low interest rates has been implemented. This policy provides opportunities for business development and new investment in the livestock industry in NTT Province. Various patterns/schemes of soft credit and simple procedures and directly to livestock farmer groups such as Strengthening Group Business Capital (PMUK) or Community Direct Loan Assistance (BPLM) or Social Assistance Patterns are actually very good opportunities to overcome the problem of capital difficulties for farmers. Through through and intensification with the support of technology with prospects to increase productivity as well. The role of the sub-sector in the future in Kupang Regency is still large as a provider of food from livestock as a source of income and as a job opening.